Medical Research for Hire: The Political Economy of Pharmaceutical Clinical Trials - Fisher, Jill A (Critical Issues in Health and Medicine, 2008)
Today, more than 75 percent of pharmaceutical drug trials in the United States are being conducted in the private sector. Once the sole province of academic researchers, these important studies are now being outsourced to non-academic physicians. According to Jill A. Fisher, this major change in the way medical research is performed is the outcome of two problems in U.S. health care: decreasing revenue for physicians and decreasing access to treatment for patients. As physicians report diminishing income due to restrictive relationships with insurers, increasing malpractice insurance premiums, and inflated overhead costs to operate private practices, they are attracted to pharmaceutical contract research for its lucrative return. Clinical trials also provide limited medical access to individuals who have no or inadequate health insurance because they offer "free" doctors' visits, diagnostic tests, and medications to participants. Focusing on the professional roles of those involved, as well as key research practices, Fisher assesses the risks and advantages for physicians and patients alike when pharmaceutical drug studies are used as an alternative to standard medical care. A volume in the Critical Issues in Health and Medicine series, edited by Rima D. Apple and Janet Golden